1996
DOI: 10.1074/jbc.271.42.26302
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Lithostathine as a Calcite Habit Modifier

Abstract: Most biological fluids are supersaturated with calcium salts. A mechanism controlling crystal growth is therefore necessary to prevent excessive precipitation and development of a lithiasis. In pancreatic juice, calcite precipitation is prevented by lithostathine, a glycoprotein that inhibits calcite crystal growth. We describe here the interaction of lithostathine with calcite crystals. Without lithostathine, calcite crystals grew as rhombohedra showing six (104) faces. At low concentration (1 microM), lithos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Structural studies of ovocleidin-17 and ansocalcin revealed that their three-dimensional structure is very similar to the structure of lithostathine (Bertrand et al, 1996;Lakshminarayanan et al, 2005;Reyes-Grajeda et al, 2004); however, the three proteins had different effects on calcium carbonate crystals. Lithostathine was an inhibitor, ansocalcin caused the formation of crystal aggregates, and ovocleidin-17 led to the crystals twinning (but not to an extensive aggregation of crystals like with ansocalcin) (Geider et al, 1996;Lakshminarayanan et al, 2005). It should be noted that N-terminal regions of ansocalcin and ovocleidin-17 are well folded, while lithostathine's N-terminus is disordered.…”
Section: Egg Shell Related Idpsmentioning
confidence: 99%
“…Structural studies of ovocleidin-17 and ansocalcin revealed that their three-dimensional structure is very similar to the structure of lithostathine (Bertrand et al, 1996;Lakshminarayanan et al, 2005;Reyes-Grajeda et al, 2004); however, the three proteins had different effects on calcium carbonate crystals. Lithostathine was an inhibitor, ansocalcin caused the formation of crystal aggregates, and ovocleidin-17 led to the crystals twinning (but not to an extensive aggregation of crystals like with ansocalcin) (Geider et al, 1996;Lakshminarayanan et al, 2005). It should be noted that N-terminal regions of ansocalcin and ovocleidin-17 are well folded, while lithostathine's N-terminus is disordered.…”
Section: Egg Shell Related Idpsmentioning
confidence: 99%
“…DC-SIGN contains the highly conserved Glu-Pro-Asn (EPN) motif and thus belongs to the mannose-specific family of lectins (31). Nonetheless, the CRDs of C-type lectins can recognize a remarkably broad range of ligands and have also been shown to bind specifically to proteins (34), lipids (35), and inorganic molecules such as calcium carbonate (36). Moreover, some CRDs are able to bind to both protein and saccharide ligands (37,38).…”
mentioning
confidence: 99%
“…In contrast, studies using full proteins were non-quantitative and underlying sources of growth modification were ill-defined. [7,8] Here we investigate interactions between proteins isolated from abalone shell nacre and growing surfaces of calcite. We find that these proteins significantly accelerate the molecular-scale kinetics and, though much larger than atomic steps, alter growth morphology through stepspecific interactions that lower their free energies.…”
mentioning
confidence: 99%